Peri-implant mucosal tissue attachment: Narrative review - Suzie Choe; Tao Ma; Deborah Jones; Harlan J. Shiau; Hanae Saito (Elsevier, 2024)
The peri‑implant mucosa (PIM) is formed during the wound healing process that follows implant and abutment placement. The PIM is known to play crucial roles in function; acting as a biologic barrier for bacterial infiltration and maintaining the mucosal health of the implant, and for implant esthetics. This narrative review presents:• Differences between periodontal soft tissue attachment and peri‑implant mucosal tissue attachment• Development of the osseointegration and its effect on PIM• Different Implant - abutment interface configurations including one- VS two-piece implants, bone-level VS tissue-level implants, and PIM in different implant collars• Engineering in surface characteristics